Spontaneous and Engineered Deletions in the 3′ Noncoding Region of Tick-Borne Encephalitis Virus: Construction of Highly Attenuated Mutants of a Flavivirus - Mandl, Christian W. (American Society for Microbiology, 1998)
The flavivirus genome is a positive-strand RNA molecule containing a single long open reading frame flanked by noncoding regions (NCR) that mediate crucial processes of the viral life cycle. The 3′ NCR of tick-borne encephalitis (TBE) virus can be divided into a variable region that is highly heterogeneous in length among strains of TBE virus and in certain cases includes an internal poly(A) tract and a 3′-terminal conserved core element that is believed to fold as a whole into a well-defined secondary structure. We have now investigated the genetic stability of the TBE virus 3′ NCR and its influence on viral growth properties and virulence. We observed spontaneous deletions in the variable region during growth of TBE virus in cell culture and in mice. These deletions varied in size and location but always included the internal poly(A) element of the TBE virus 3′ NCR and never extended into the conserved 3′-terminal core element. Subsequently, we constructed specific deletion mutants by using infectious cDNA clones with the entire variable region and increasing segments of the core element removed. A virus mutant lacking the entire variable region was indistinguishable from wild-type virus with respect to cell culture growth properties and virulence in the mouse model. In contrast, even small extensions of the deletion into the core element led to significant biological effects. Deletions extending to nucleotides 10826, 10847, and 10870 caused distinct attenuation in mice without measurable reduction of cell culture growth properties, which, however, were significantly restricted when the deletion was extended to nucleotide 10919. An even larger deletion (to nucleotide 10994) abolished viral viability. In spite of their high degree of attenuation, these mutants efficiently induced protective immune responses even at low inoculation doses. Thus, 3′-NCR deletions represent a useful technique for achieving stable attenuation of flaviviruses that can be included in the rational design of novel flavivirus live vaccines.